Saline groundwater surface water interaction in coastal lowlands - Delsman, Joost R. (Deltares select series, 2015)
Coastal zones are among the world's most densely populated and economically important areas, but these factors put pressure on the often limited available freshwater resources. Global change will undoubtedly increase this pressure through the combined effects of increased population, economic development, rising sea levels, increased evapotranspiration, over-extraction and the salinization of coastal aquifers, decreasing river discharges, and accelerating land subsidence.Saline groundwater exfiltration is a common problem in the coastal zone of the Netherlands, but the hydrological processes and physiographic factors that affect this are not fully understood. The research presented in this book aims to identify the processes and physiographic factors controlling the spatial variability and temporal dynamics of the exfiltration of saline groundwater to surface water, and hence the contribution of saline groundwater to surface water salinity. Topics covered include a paleo-hydrogeological model simulation of the Holocene evolution of groundwater salinity as a result of paleo-geographic changes; surface water salinity dynamics in a densely-drained lowland catchment; hydrograph separation in an agricultural catchment; observations of heads, flow, solute concentration and temperature to constrain a detailed, variable-density groundwater flow and transport model; and a model to simulate the salinity dynamics of exfiltrating groundwater to support operational water management of freshwater resources in coastal lowlands. The book further outlines the implications of these findings for freshwater management in the Netherlands. The book demonstrates that the salinity of groundwater exfiltrating in polders in the Netherlands, and hence surface water salinity, varies on a wide range of spatial and temporal scales.